Unraveling energy homeostasis in a dynamic model of glycolysis in Escherichia coli - Giordano, Giulia; De Graaf, Lotte M.; Vasilakou, Eleni; Wahl, Sebastian Aljoscha (2019 18th European Control Conference, ECC 2019, 2019)
We study dynamic metabolic models that describe the cellular responses of microorganisms under changing environmental conditions, such as substrate perturbations. Feast-famine experiments in Escherichia coli show that, despite the enormous extracellular perturbations, important quantities such as the cell energy charge remain practically constant. We propose a simplified kinetic model of glycolysis in E. coli and we analyse it to investigate the mechanisms that guarantee the observed homeostatic energy charge. Identifying the source of this extraordinary robustness will streamline the synthesis of robust and efficient 'cell factories' for the production of relevant chemicals, enabling sustainable processes.
CRIS-Team Scopus Importer:2022-01-11